(3TQM GddeYJjfs - (3GdHjGJj, GdfLaj, GdCMeOj, edG cJGH, eMeO LhGO Hf eMeO Jbj Hf eMeO, (B( (3cGf MjG (B1267 (3g` (B)s
(3ChdgG (B:s
(3CMeOg Ydi fhGdg (B... (3gPg MhGT JJVe ahGFO de CSHb EdjgG hYhGFO de CTQc GdJfHjg YdjgG ehSheI HGdaPGdc JLQj eLQi GdTQM Ydi cJGHj GdeOGQc hGdeSGdc aj TQM TQGFY GdESdGe GdeTJgQ Hjf GdNhGU hGdYhGe (B...s
(3BNQgG (B:s
... (3hZjQ Pdc eeG PcQg GdCUMGH aj cJHge GdeWhdI hcJH GdGYeGd hdG MUQ dfbd GdUdGI aEf bQHGf cd Jbj hNjQ ehVhY bef TGA GSJbd hef TGA GSJcKQ ceG Sda HjGfg aj Ghd GdcJGH hbO Je GdLRA efg (B.s
(3JHUQI GdYfhGf (B:s
(3hjSei (B: (3TQM GddeYJjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\201s
(3eYLe GdeDdajf (B3\201s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis